Google talking - Baskin, Brian (Syngress, 2007)
Nationwide and around the world, instant messaging use is growing, with more than 7 billion instant messages being sent every day worldwide, according to IDC. comScore Media Metrix reports that there are 250 million people across the globe--and nearly 80 million Americans--who regularly use instant messaging as a quick and convenient communications tool. Google Talking takes communication to the next level, combining the awesome power of Text and Voice! This book teaches readers how to blow the lid off of Instant Messaging and Phone calls over the Internet. This book will cover the program Google Talk in its entirety. From detailed information about each of its features, to a deep-down analysis of how it works. Also, we will cover real techniques from the computer programmers and hackers to bend and tweak the program to do exciting and unexpected things. * Google has 41% of the search engine market making it by far the most commonly used search engine * The Instant Messaging market has 250 million users world wide * Google Talking will be the first book to hit the streets about Google Talk.
Print version record
Keywords: Google Talk (Computer File); Instant messaging; Internet telephony; Google Talk (Computer file); Messagerie instantanée; Téléphonie Internet; Science_and_Technology; COMPUTERS; System Administration; Email Administration